PENGELOLAAN BUMDES “CIJEUNGJING BERDIKARI” SEBAGAI PENGGERAK PEREKONOMIAN DESA - Pipih Sopiah; Sirodjul Munir; Neti Sunarti (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze the management of the Village-Owned Enterprise (BUMDes) 'Cijeungjing Berdikari' as a driver of the economy of Cijeungjing Village, Cijeungjing District, Ciamis Regency. Using a descriptive qualitative approach, this study focuses on the implementation of management functions according to George R. Terry which include planning, organizing, implementing, and monitoring. The results of the study indicate that BUMDes "Cijeungjing Berdikari" has a fairly good institutional basis, but its implementation still encounters obstacles such as minimal human resources, the absence of SOPs and written job descriptions and a lack of business development innovation. To realize BUMDes as an optimal driver of the village economy, it is necessary to increase human resource capacity, strengthen supervision, and adequate capital support.